Analisis Manajemen Kualitas dan Design Produk Menggunakan Metode Quality Function Deployment (QFD) pada Kongsi Coffee Shop di Kota Pangkalpinang - Orivia Aryan, Lola; Ruben Manullang, Rizal; Panjaitan, Ferry (Jurnal Progresif Manajemen Bisnis, 2024)
This research aims to analyze the overall level of customer satisfaction by looking at and knowing the level of importance of service/product attributes. at Kongsi coffee shop in Pangkalpinang city. Using a quantitative approach with a descriptive framework, this research uses the KANO and QFD models as analysis methodology. Two data analysis tools were used, namely the Importance Performance Analysis method and the Customers Satisfaction Index through validity tests and reliability tests calculated using JASP. This study involved 20 respondents, this analysis identified five main categories, namely economy, ergonomics, durability, performance and features. The results of the research show that in the economic dimension it has a high level of importance (4.0667) and good performance (4.45), being in the upper right quadrant indicating that the Kongsi Pangkal Pinang café meets consumer expectations well and needs to be maintained. The ergonomic dimension has a fairly high level of importance (4.0167) but low performance (3.35), being in the upper left quadrant, indicating that significant improvements are needed to increase performance. The durability dimension has a fairly high level of importance (4.0167) but low performance (3.35), being at the top left indicates that significant improvements are needed. The performance and feature dimensions have a high level of importance (4.05 and 4.0333), but less satisfactory performance (3.2833 and 3.35), indicating that improvements are needed to improve the performance of these two dimensions